Neuroprotective effect of tempeh against lipopolysaccharide-induced damage in BV-2 microglial cells. (2nd December 2019) - Hwang, Juen-Haur; Wu, Shu-Jing; Wu, Po-Long; Shih, Yong-Yao; Chan, Yin-Ching
Abstract : Objectives: This study evaluated the bioactive composition of tempeh products and examined the effects of tempeh on BV-2 microglial cell cytotoxicity, neurotrophic effects, and expression of inflammatory genes. Methods: Tempeh products included soybean fermented by Rhizopus, soybean fermented through cocultivation with Rhizopus and Lactobacillus, and red bean fermented through cocultivation with Rhizopus and Lactobacillus (RT-C). We analyzed the bioactive contents of tempeh extracts and evaluated the effects of tempeh water extract on lipopolysaccharide (LPS)-treated BV-2 cells. Results: The results showed that RT-C water extract had the highest concentrations of γ-aminobutyric acid (GABA) and anthocyanin. The tempeh water extracts, especially RT-C, reduced the formation of LPS-induced reactive oxygen species, downregulated the levels of nitric oxide synthase and phospho-cyclic-AMP response element-binding protein, and upregulated the expression of brain-derived neurotrophic factor (BDNF). Discussion: Our data demonstrate that RT-C has the highest concentrations of GABA and anthocyanin, more effectively reduces oxidative stress and inflammation, and increases the expression of BDNF in LPS-induced BV-2 cells.